Exploring Current and Future Research Trends on Safety Climate in Construction Projects - Kajumulo, Kamugisha J.; Matindana, Juma M.; Mohamed, Fatma K. (Tanzania Journal of Engineering and Technology, 2023)
Both clients, consultants, and contractors in the construction industry can benefit from a safety climate by obtaining knowledge of attitudes and perceptions for better safety outcomes. However, the current and future research trends for safety climate in construction projects have not yet been fully examined. In order to solve this problem, a systematic review of previous research findings using a social network approach must be conducted, and future trends for the safety climate in building projects must be identified. Sixty-three peer-reviewed articles were gathered to study the literature on safety climate in construction projects. A social network approach was employed using VOS viewer to look at the connections between the researchers and the article's keywords. Based on the frequency of researcher collaboration and the connections between the keywords used in the publications, five research groups and four keyword themes were identified using the social network analysis results. The scholars received substantial implications and insights on the state of the research and future directions, which helped create a focused development strategy for safety climate in construction projects. The scope of this study is limited to publications on the subject matter from 2000 to 2021, which provided the base for the current and future research trends on safety climate in construction projects. The findings from this social network analysis revealed that studies on safety climate are more skewed to the organizational level than the projects level. In developing countries like Tanzania, studies are scanty. Also, different levels of decision-making within the organization and within construction projects, call for different safety factors whereby the current studies have slightly considered such a fact. Furthermore, it is the right time now for researchers to focus on developing a safety climate maturity framework for construction projects. Keywords: Safety climate; construction industry safety; Safety for workers; construction projects; social network analysis.